2009
DOI: 10.1172/jci38468
|View full text |Cite
|
Sign up to set email alerts
|

Aberrantly glycosylated IgA1 in IgA nephropathy patients is recognized by IgG antibodies with restricted heterogeneity

Abstract: IgA nephropathy (IgAN) is characterized by circulating immune complexes composed of galactose-deficientIgA1 and a glycan-specific IgG antibody. These immune complexes deposit in the glomerular mesangium and induce the mesangioproliferative glomerulonephritis characteristic of IgAN. To define the precise specificities and molecular properties of the IgG antibodies, we generated EBV-immortalized IgG-secreting lymphocytes from patients with IgAN and found that the secreted IgG formed complexes with galactose-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
398
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 297 publications
(426 citation statements)
references
References 49 publications
16
398
1
6
Order By: Relevance
“…In this work, we demonstrate the complete analysis of O-glycoform microheterogeneity and site localization of the glycoforms in a naturally Gal-deficient IgA1 (Ale) myeloma protein that mimics the nephritogenic IgA1 in patients with IgAN (8,9). Reversed phase (RP) LC FT-ICR MS successfully identified 10 distinct IgA1 HR fragments representing Ͼ99% of total IgA1.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we demonstrate the complete analysis of O-glycoform microheterogeneity and site localization of the glycoforms in a naturally Gal-deficient IgA1 (Ale) myeloma protein that mimics the nephritogenic IgA1 in patients with IgAN (8,9). Reversed phase (RP) LC FT-ICR MS successfully identified 10 distinct IgA1 HR fragments representing Ͼ99% of total IgA1.…”
mentioning
confidence: 99%
“…This distinctive IgA1 is in circulating immune complexes (8,10,15) and in the glomerular deposits of IgAN patients (16,29). The absence of Gal apparently leads to the exposure of neoepitopes, including terminal and sialylated N-acetylgalactosamine (GalNAc) residues (9,10). These epitopes are recognized by naturally occurring antiglycan IgG or IgA1 antibodies and, consequently, circulating immune complexes are formed (9,10,15) that can deposit in the glomerular mesangia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…IgA1 is unusual in that it has a heavily O-glycosylated hinge region between the CH1 and CH2 domains of the a H chain (1,2). The presence of poorly galactosylated IgA1 O-glycoforms in the serum of patients with IgAN favors formation of circulating immune complexes (IC), which are prone to deposition in the glomerular mesangium (3)(4)(5)(6). Once deposited, these IgA IC trigger mesangial cell activation.…”
mentioning
confidence: 99%
“…[66][67][68] Interestingly, it has been shown that dimers and polymers of IgA aggregate more readily than monomers, 69 which might explain the propensity of this form to aggregate and deposit in tissues. Our group has also shown that aberrant glycosylation of IgA1 and IC formation constitute essential factors favoring mesangial IgA1-TfR interactions as initial steps in IgAN pathogenesis.…”
Section: Iga Dysfunction and Inflammatory Diseases C Papista Et Al 129mentioning
confidence: 99%